The Effect of Starbucks Reward Marketing Communications on Instagram @starbucksindonesia on Followers Buying Interest - Farhan, Muhammad Yoga; Nugrahaeni, Elisabeth; Putri, Kinkin Yuliaty Subarsa (Tecno Scientifica Publishing, 2024)
The development of technology has significantly influenced various aspects of life, particularly in communication and business, which are closely interconnected. In marketing, effective communication plays a crucial role, a concept known as marketing communication. In today's digital era, most activities are conducted online, making marketing communications increasingly reliant on online media. Marketing communication is a strategic activity aimed at creating awareness or knowledge about products and their attributes, informing consumers about product benefits, building a positive image, and fostering positive attitudes, preferences, and buying interest in the product. This research aims to examine the effect of Starbucks Reward marketing communications on Instagram @starbucksindonesia on followers' buying interest. A quantitative research approach with a survey method was employed. The population for this study consisted of followers of the Instagram account @starbucksindonesia, with a sample size of 100 participants. The research findings indicate that the calculated t-value was 9.091, which is greater than the critical t-value of 1.995 (9.091 > 1.995). The significance value was 0.000, which is less than the threshold of 0.05 (0.000 < 0.05). These results demonstrate a significant influence of the independent variable X (Marketing Communications) on the dependent variable Y (Buying Interest).